Organic acids produced by lactobacilli, enterococci and yeasts isolated from Picante cheese - Freitas, A. Cristina (2011)
Four species of bacteria (Enterococcus faecium and Enterococcus faecalis, Lactobacillus plantarum and Lactobacillus paracasei) and three species of yeasts (Debaryomyces hansenii, Yarrowia lipolytica and Cryptococcus laurentii), previously isolated from Picante cheese, were cultured in ovine and in caprine milk and assayed for sugar and organic acids metabolism for 6 days. The results indicated that both milk types can be coagulated by the four strains of lactic acid bacteria. Lb. paracasei led to a faster and greater reduction in pH. Production of lactic acid correlated to lactose degradation, and was highest for Lb. paracasei followed by E. faecium; citrate metabolism was apparent for E. faecalis and, to a lesser extent, for E. faecium, Lb. plantarum and Lb. paracasei. Relatively high contents of formic acid were found when inoculation was with Enterococcus and with Lb. plantarum.